The development and evaluation of an intervention to promote the uptake of preventive tasks by occupational physicians targeting work-related mental health problems: protocol for the IM-PROmPt-study - S. Orhan Pees; S. H. van Oostrom; F. G. Schaafsma; K. I. Proper (BMC, 2023)
Abstract Objective Work-related mental health problems are a major and growing public and occupational health issue. Although prevention of work-related disease is a central task in the work of occupational physicians, implementation of preventive tasks can still improve. The aim of this paper is to present the development of an intervention to support occupational physicians in the execution of preventive tasks and a protocol for its evaluation. Methods An intervention to support occupational physicians has been developed making use of the implementation mapping protocol. The intervention was based on barriers and facilitators for the execution of preventive tasks, input from stakeholders, and evidence-based strategies from literature. Results The intervention consists of three peer group supervision meetings directed to preventive tasks. During these meetings, occupational physicians will receive materials and will use goal-setting to formulate their own action plans. The IM-PROmPt-study (Implementation of PReventive tasks by Occupational Physicians) is a two-armed cluster randomized controlled trial, comparing peer group supervision directed to the implementation of preventive tasks for occupational physicians with usual peer group supervision. The evaluation will include an effect and process evaluation to examine if the intervention is successful in supporting OPs to implement preventive activities, specifically aimed to prevent work-related mental health problems. Discussion The intervention is expected to lead to more knowledge and awareness of the value of prevention among OPs, anticipated to lead to both organizational and individual gains. Trial registration ISRCTN registry; ISRCTN15394765. Registered on 27 June 2023.